Histone demethylases in physiology and cancer: a tale of two enzymes, JMJD3 and UTX. (February 2016) - Arcipowski, Kelly Marie; Martinez, Carlos Alberto; Ntziachristos, Panagiotis
Abstract : Gene regulation is fine-tuned by a dynamic balance between transcriptionally activating and repressive modifications of histone tails. It has been well-established that lysine and arginine methylation can be reversed by two groups of evolutionarily conserved enzymes known as histone demethylases, which have been shown to play critical roles in development, differentiation and diseases like cancer. Recent work has demonstrated demethylase-independent functions of these proteins, highlighting the complex mechanisms by which these proteins exert their effects on gene expression. Here, we discuss the roles of lysine 27 demethylases, JMJD3 and UTX, in cancer and potential therapeutic avenues targeting these enzymes. Despite a high degree of sequence similarity in the catalytic domain between JMJD3 and UTX, numerous studies revealed surprisingly contrasting roles in cellular reprogramming and cancer, particularly leukemia. Understanding the demethylase-dependent and demethylase-independent functions of the enzymes affecting histone methylation, their post-translational modifications and participation in different complexes, as well as in vivo modeling of the mutations affecting those enzymes in cancer, can shed light on their unique physiological roles. This information cumulated in the future will aid in the development of improved inhibitors to treat cancers affected by demethylase mutations and aberrant gene activation.